2004
DOI: 10.1080/0003684042000306923
|View full text |Cite
|
Sign up to set email alerts
|

Economic growth and government expenditure: evidence from a new test specification

Abstract: A new test specification of Wagner's Law of Public Expenditure has been formulated. The aim is to disentangle the effects of accelerating and decelerating economic growth on growth in government expenditure. Two alternative proxies for the state of the economy are experimented with. The first defines the current state of the economy by relating it to its historical mean growth rate, while the second defines it relative to a pooled time-series/cross-sectional mean growth rate. This distinction is then explicitl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 14 publications
0
29
0
7
Order By: Relevance
“…The third part involves the researches using bounds test which is based on the unrestricted error correction model (UECM) proposed by Pesaran et al (2001). This test procedure can be applied irrespective of whether the explanatory variables are I(0) or I(1) and to the studies with samples in small scale (Wahab, M., 2004, Chiung. 2006, Emmanuel, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…The third part involves the researches using bounds test which is based on the unrestricted error correction model (UECM) proposed by Pesaran et al (2001). This test procedure can be applied irrespective of whether the explanatory variables are I(0) or I(1) and to the studies with samples in small scale (Wahab, M., 2004, Chiung. 2006, Emmanuel, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…2 For example, Chow et al (2002), Thornton (1999) and Ansari et al (1997) have found evidence in support of Wagner's law. However, Ram (1986), Afxentiou and Serletis (1996) and Wahab (2004) failed to find evidence in support of Wagner's law. Some studies have however, found evidence in support of both Wagner and Keynesian hypotheses.…”
Section: Introductionmentioning
confidence: 85%
“…Additionally, they also failed to detect causality from GDP to these spending categories thus rejecting Wagner's law. Others, rejecting Wagner's law in developed countries include Wahab (2004) and Ram (1986). Al-Yousif (2008) using the time-series data examined the direction of relationship between education spending and economic growth in the six GCC economies over the period 1977-2004.…”
Section: An Overview Of the Literature On Public Spending And Economimentioning
confidence: 98%
“…Chang, Liu, and Caudill (2004) discovered support for Wagner's law in five countries out of a sample of ten countries. Wahab (2004), and Kolluri and Wahab (2007) suggested that Wagner's law is valid when GDP growth decelerates to below the trend for the OECD countries group, while it is invalid when GDP growth accelerates above the trend. Lamartina and Zaghini (2011) provided evidence for the validity of Wagner's law in 23 OECD countries.…”
Section: Literature Reviewmentioning
confidence: 99%